Understanding Language Teachers’ ICT Uptake from Ecological Perspectives - Justsinta Sindi Alivi; Rym Boudjouada; Hajar Nurma Wachidah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This paper summaries factors affecting teachers’ decision to use ICT (Information and Communication Technology) in teaching modern languages. This paper tries to understand the teachers’ ICT uptake from ecological perspective discussing that teachers’ attitudes are influenced by environments in different levels (e.g. micro, meso, macro). In this paper, the environments refer to micro as teacher, meso as institution, and macro as beyond institution levels. Teacher levels define the aspects related to teachers’ psychological and demographic characteristics. Institutions levels describe the teachers’ decision from the influence of support and social circle in the institution. Beyond institution levels discuss the influence from wider environments such as government and public demand.